2022
DOI: 10.1097/md.0000000000030455
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma fibrinogen degradation products(FDP) and D-dimer levels and disease activity in rheumatoid arthritis: A STROBE compliant article

Abstract: In this study, we aimed to investigate whether fibrinogen degradation products(FDP)and D-dimer could be used as serological indicators of rheumatoid arthritis(RA) activity, such as erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and platelets (PLT).A total of 112 consecutive patients with RA between July 2018 and July 2020 were divided into moderate and high disease activity groups (disease activity score 28(DAS28) > 3.2, n = 60) and low disease activity and remission groups (DAS28≤3.2, n = 52)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Asthmatic patients revealed strong positive associations between fibrinogen and both ESR and pre-treatment CRP, while YKL-40 appeared to be independent of the other variables analyzed. These findings may reflect the well-known fact that fibrinogen, CRP, and ESR are general markers of systemic inflammation and tend to be directly related to each other even in healthy subjects [ 41 , 42 ]. The most significant correlations in COPD patients were, by contrast, found for YKL-40; that is, negative association with lymphocyte-related parameters and positive, but weaker association with neutrophil-related parameters.…”
Section: Discussionmentioning
confidence: 78%
“…Asthmatic patients revealed strong positive associations between fibrinogen and both ESR and pre-treatment CRP, while YKL-40 appeared to be independent of the other variables analyzed. These findings may reflect the well-known fact that fibrinogen, CRP, and ESR are general markers of systemic inflammation and tend to be directly related to each other even in healthy subjects [ 41 , 42 ]. The most significant correlations in COPD patients were, by contrast, found for YKL-40; that is, negative association with lymphocyte-related parameters and positive, but weaker association with neutrophil-related parameters.…”
Section: Discussionmentioning
confidence: 78%
“…The 31 selected studies, including a total of 36 group comparators, assessed the D-dimer in 2724 RD patients (mean age 46 years, 75% females) and 3437 healthy controls 62,63,66,75,79,80,[82][83][84][85][86][88][89][90][91][92] Europe (n = 12), 64,[67][68][69][70][71][72][73][74][76][77][78] America (n = 2), 81,87 and Oceania (n = 1). 65 RA was investigated in 10 study groups, [66][67][68][69][70][71]73,79,88,91 SLE in nine, 66,72,75,[81][82][83]86,87,89 BD in three,…”
Section: Resultsmentioning
confidence: 99%
“…65 RA was investigated in 10 study groups, [66][67][68][69][70][71]73,79,88,91 SLE in nine, 66,72,75,[81][82][83]86,87,89 BD in three, 62,76,77 AAV in three, 78,83,84 spondyloarthritis (SpA) and AS in three, 70,85,90 SSc in two, 64,74 OA in two, 65,70 gout in one, 80 crystal arthritis in one, 70 Takayasu arteritis (TA) in one, 63 and primary Sjögren's Syndrome (pSS) in one. 92 Twenty-four studies were prospective [62][63][64][65][66][67][68][69][70][71][73][74][75]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have confirmed the correlation between D-dimer levels and rheumatoid arthritis activity indices through retrospective data mining [ 26 ]. In addition to its predictive value for the diagnosis of VTE in CTD patients [ 27 ], it has been shown that D-dimer level is also a valid serologic index for assessing disease activity in some CTD patients [ 28 , 29 ]. D-dimer can be used as one of the effective monitoring indicators during the suppression of hypercoagulability due to immune activity with glucocorticoids.…”
Section: Vte Associated With the Systemic Inflammatory Responsementioning
confidence: 99%